-5x + 4x = -6 Combining like terms: -x = -6 Multiplying by -1 (or switching signs): x = 6
-1x-4-4x= -5x-4so it is -5x-4 -5x - 4this is done by combining like terms.
To simplify the expression 8x - 8 - 4x - 3 - 3x, first combine like terms. Start by combining the x terms: 8x - 4x - 3x = x. Then, combine the constant terms: -8 - 3 = -11. Therefore, the simplified expression is x - 11.
Collecting like terms they are equal to: 2x+6y
6x + 14 = 20 + 4x ------ Combine like terms (subtract 4x and 14 from both sides). 2x = 6 --------------------- Divide by 2. x = 3
-5x + 4x = -6 Combining like terms: -x = -6 Multiplying by -1 (or switching signs): x = 6
-1x-4-4x= -5x-4so it is -5x-4 -5x - 4this is done by combining like terms.
4x + -x = 3x
collect like terms and you get 4x + 5x + 8 - 3 ie 9x +5
3x + x = 4x
-1
no,, to be like term they must have the same variable,, such as 4x and 9x.. or 1y and 300y...
4y + 3w + 4x + 9y + 7x - 7w (combine like terms)-4w + 11x + 13y
Combine like terms, meaning add 12X plus 4X which is 16X and then you add 25Y plus 15Y which equals 40Y so the answer will be 16x+40y. combine like terms means add the ones with the same variable.
x+5+3x-7+9x+3-4x Collect like terms: 9x+1
To simplify the expression 8x - 8 - 4x - 3 - 3x, first combine like terms. Start by combining the x terms: 8x - 4x - 3x = x. Then, combine the constant terms: -8 - 3 = -11. Therefore, the simplified expression is x - 11.
Collecting like terms they are equal to: 2x+6y